DiGAlign: Versatile and Interactive Visualization of Sequence Alignment for Comparative Genomics - Nishimura, Yosuke; Yamada, Kohei; Okazaki, Yusuke; Ogata, Hiroyuki (Microbes and Environments, 2024)
With the explosion of available genomic information, comparative genomics has become a central approach to understanding microbial ecology and evolution. We developed DiGAlign (https://www.genome.jp/digalign/), a web server that provides versatile functionality for comparative genomics with an intuitive interface. It allows the user to perform the highly customizable visualization of a synteny map by simply uploading nucleotide sequences of interest, ranging from a specific region to the whole genome landscape of microorganisms and viruses. DiGAlign will serve a wide range of biological researchers, particularly experimental biologists, with multifaceted features that allow the rapid characterization of genomic sequences of interest and the generation of a publication-ready figure.